Double Loop Poblem Solving Learning Models on The Students' Mathematical Literacy Skills - Nur, Fitriani; Halimah, Andi; Yovita, Devina Oktari; M, Munawarah; Thalhah, Sitti Zuhaerah (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2019)
This research aims to: (1) find out the differences in mathematical literacy skills of students using the DLPS learning model and those using conventional learning models, (2) find out the differences in students' mathematical literacy skills in terms of verbal skills of students, (3) to find out the interaction of the DLPS learning model in terms of students' verbal skills on mathematical literacy skills of students. The research approach uses a quantitative approach with the type of quasi-experimental research and design of Factorial design 3 x 2. The population in this study is all eighth grade students of MTs Muhammadiyah Kampung Baru with the total is 48 people. The sample in this study is the eight-grade A  as a control class while the eight grade B is  as an experimental class. The instrument used in this study is a test of students 'mathematical literacy skills in the form of pretest and posttest and questionnaires to measure students' verbal skills. The data analysis technique used are descriptive statistical analysis and inferential statistical analysis. The result shows that: (1) there is a difference between the application of the DLPS learning model and the conventional model on the mathematical literacy skills of students, (2) there is a difference in students' mathematical literacy skill in terms of vebal skill of students, and (3) there is no interaction effect between the DLPS learning model in terms of verbal skill to mathematical literacy skills of students